2020
DOI: 10.1016/j.toxrep.2020.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, stability and risk assessment for sulfonamides and tetracyclines in aqua-cultured Nile Tilapia fish of Egypt

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The findings of the current study showed that TCs (with high detection frequencies of 58.3% and 62.5%) were often used by farmers to monitor fish health and treat diseases, without adhering to the recommended withdrawal period for these antibiotics. Additionally, in some cases, the reason for high levels of tetracycline antibiotics in fish samples could be the use of substances containing antibiotics, like poultry manure, to improve plankton growth in aquaculture systems [ 43 ]. The maximum residual limits (MRL) of 100 μg/kg established by the European Commission [ 14 ] were not exceeded in any of the present study's tilapia samples that were contaminated with TCs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings of the current study showed that TCs (with high detection frequencies of 58.3% and 62.5%) were often used by farmers to monitor fish health and treat diseases, without adhering to the recommended withdrawal period for these antibiotics. Additionally, in some cases, the reason for high levels of tetracycline antibiotics in fish samples could be the use of substances containing antibiotics, like poultry manure, to improve plankton growth in aquaculture systems [ 43 ]. The maximum residual limits (MRL) of 100 μg/kg established by the European Commission [ 14 ] were not exceeded in any of the present study's tilapia samples that were contaminated with TCs.…”
Section: Resultsmentioning
confidence: 99%
“…The data in Table 3 demonstrated that SA, including the SMX, was below the limit of quantification (<LOQ) in the samples from the retail centre. [ 43 ] found SMX in tilapia in El-Fayoum in another Egyptian study, with a mean concentration of 52.41 μg/kg. In a study conducted by Ref.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tetracyclines, which have a bacteriostatic effect by inhibiting the protein synthesis of bacteria, are one of the most widely used antibiotic groups for therapeutic and prophylactic purposes in aquaculture (Ahmed et al., 2020; Morshdy et al., 2022). Doxycycline (DO), a second‐generation, semi‐synthetic tetracycline derivative antibacterial drug, has a broad‐spectrum bacteriostatic activity against a wide range of gram‐positive and gram‐negative bacteria as well as many protozoa (Bilen & Elbeshti, 2019; del Castillo, 2013; Holmes & Charles, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Fish farming possesses a major share for Egypt agriculture income [1], as well as a vital source of income for people living along the coast and the Nile River, in addition to the fisheries in the canals, river Nile, lakes, ponds, Mediterranean Sea, and Red Sea that are considered other key activities in the country. Despite this, the country's gross domestic product is dominated by fisheries, it also contributes to foreign exchange revenues by exporting [2].…”
Section: Introductionmentioning
confidence: 99%